CULTURAL EMPLOYEE EMPLOYEES ACCREDITED (Study of Social Reality Concerning Employee Behavior of District General Hospital "Kanjuruhan" Kepanjen District Accredited) - *, Dr. Susilowati (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study raises the background on the Working Culture of Accredited Hospital Staff (Social Reality Study Concerning Employee Behavior of District General Hospital "Kanjuruhan" Kepanjen Malang Regency). Problems raised in this study are: How Employment Culture Employees Regional General Hospital "Kanjuruhan" Kepanjen Malang Regency Accredited as well as what factors underlying Working Culture Employees Regional General Hospital "Kanjuruhan" Kepanjen Malang Regency. Using a qualitative description approach with ground theory, as for who is the subject of this study are the employees at the Regional General Hospital "Kanjuruhan" Kepanjen Malang Regency. Sampling in this research using purposive sampling, and with support of primary data through observation, indepth interview with informant yan spread in environment General Hospital "Kanjuruhan" Kepanjen Kabuputen Malang. Secondary data that support the overall expected outcome of this research are a number of written documents either in the form of related references in the form of textbooks as well as written regulations in such decisions, regulations, and others that have relevance. The results of this study reveal a number of very significant findings which subsequently formed a proposition. From the existing propositions can be taken a conclusion that answers the existing problems. In addition, the items from the results of this study will provide valuable input and which will be used as a better service improvement for the community as well as improving the professionalism of human resources in General Hospital Kanjuruhan Malang Regency. The theoretical implications of this study complement the Work Culture Theory by Osbourne and Plastrik (2010), that the Working Culture is a set of deeply internalized behavior, feelings, and psychological frameworks shared by members of the organization. According to the researchers, the internalized behavioral devices, feelings, and psychological frameworks are very subjective internal elements, according to these findings that the elements, Very deep and shared by members of the organization. According to the researchers, the internalized behavioral devices, feelings, and psychological frameworks are very subjective internal elements, according to these findings that these internal elements can change employee attitudes in work, from inner to other directed orientation. The major role in the internalization of these behaviors is religious values, because religious values can not only shape the work ethic, but also become drivers and inspire employees in the workplace. This opinion confirms what evolved and became a work culture in society that work was worship, and that position was a mandate. The study also supports the Social Behavior Theory, B.F. Skinner, that Social Behavior is manifested through attitudes, and feelings that can lead to relatively fixed interpersonal actions. Interpersonal events can be learned from the actions taken against the object, namely acceptance,  rejection (rejection), and avoidance (avoidance). Reality in social behavior are emerging factors such as genetic traits that are the general range of responses that can be done and affect behavior. The environment should also be considered to explain the genetic carrying.